Maturity And Governance Gap Analysis Of Simgos At Royal Maternity General Hospital Using COBIT 5 - Raisha Wafa Haibati; Justin Anggredinat; Mohd Rizky Ananda Daulay; Wilven Alberto Wu; Marlince NK Nababan (Journal of Intelligent Decision Support System (IDSS), 2026)
RSU Royal Maternity is a type C healthcare institution in Medan with full accreditation and is committed to high-quality service standards. To support the achievement of organizational objectives, Information Technology (IT) has become a strategic asset, enhancing efficiency, transparency, and service quality. However, implementing IT without proper management processes risks such as business needs disparities, reduced service quality, and system failures. This study aims to evaluate the information system governance at RSU Royal Maternity to ensure that IT investments deliver maximum added value. The research methodology uses the COBIT 5 framework, a comprehensive approach to IT governance. The analysis focuses on measuring maturity, with an emphasis on the Deliver, Service, and Support (DSS) and Monitor, Evaluate, and Assess (MEA) domains.  This focus is intended to ensure that the operations of the healthcare support system align with Standard Operating Procedures (SOPs) and professional codes of ethics. The results of this study are expected to provide recommendations for service quality improvements that will proportionally enhance patient satisfaction at Royal Maternity General Hospital.